2014
DOI: 10.1152/ajpcell.00029.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 (Sphk1) negatively regulates platelet activation and thrombus formation

Abstract: Sphingosine 1-phosphate (S1P) is a powerful regulator of platelet formation. Enzymes generating S1P include sphingosine kinase 1. The present study thus explored the role of sphingosine kinase 1 in platelet formation and function. Activation-dependent platelet integrin αIIbβ3 activation and secretion of platelets lacking functional sphingosine kinase 1 (sphk1(-/-)) and of wild-type platelets (sphk1(+/+)) were determined utilizing flow cytometry and chronolume luciferin assay. Cytosolic Ca(2+) activity ([Ca(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 58 publications
(87 reference statements)
0
15
1
Order By: Relevance
“…Hence, platelet S1P facilitates rather than inhibits platelet activation, explaining the increased aggregation reported in Sphk1-deficient platelets. 42 We show that S1P mainly induces a dose-dependent aggregation response via the S1PR 1 in whole blood. A recent study showed that aggregation of washed human platelets was reduced not only by inhibition of S1PR 1 , but also in the presence of the S1PR 2 antagonist JTE-013 40 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hence, platelet S1P facilitates rather than inhibits platelet activation, explaining the increased aggregation reported in Sphk1-deficient platelets. 42 We show that S1P mainly induces a dose-dependent aggregation response via the S1PR 1 in whole blood. A recent study showed that aggregation of washed human platelets was reduced not only by inhibition of S1PR 1 , but also in the presence of the S1PR 2 antagonist JTE-013 40 .…”
Section: Discussionmentioning
confidence: 72%
“…In our present study, we performed whole blood aggregation assays to mimic physiological conditions as closely as possible. Münzer et al 42 recently reported that Sphk1-deficient platelets show elevated degranulation (release of alpha and dense granules) and aggregation in response to low-dose agonist stimulation. Based on their findings, the authors speculated that this was because of reduced levels of intracellular platelet S1P and proposed that platelet S1P acts as a negative regulator of platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“… was ~4% lower during cycle ergometry exercise at 45% peak O 2 uptake () in extreme normobaric hypoxia (F I O 2 11%, ~5000 m). Subsequent studies have reported reductions of 4–10% (similar magnitudes to those reported in normoxia) during cycle ergometry [29, 30, 36] and treadmill running exercise [64] across a range of simulated altitudes (F I O 2 11–15.4%, ~2500–5000 m). Interestingly, one study reported lower steady-state in normobaric hypoxia (F I O 2 13.1%, ~3500 m) but not normoxia [36] following NO 3 − supplementation.…”
Section: Physiological Effects Of Nitrate (No3−) Supplementation In Hmentioning
confidence: 76%
“…This reaction is catalyzed by the NO synthase (NOS) enzymes and requires O 2 as a co-substrate. In vitro evidence suggests that NO generated via the l -arginine NOS pathway is suppressed in hypoxia [33], although in vivo evidence is less clear [3436]. Alternatively, NO can be generated via the reduction of nitrate (NO 3 − ) and nitrite (NO 2 − ) through the recently elucidated NO 3 − –NO 2 − –NO pathway [37].…”
Section: Introductionmentioning
confidence: 99%
“…After platelet activation, intracellular S1P is released into the environment3738. In vitro studies have found that arachidonic acid could stimulate platelets to secrete S1P through the activation of the thromboxane receptor38.…”
Section: Discussionmentioning
confidence: 99%